Investigation of the underlying physiological mechanisms regulating the vernal transition in mares - Sinclair, Chelsea Drumwright (Kansas State University, 2019)
The ovarian and endocrine characteristics of mares related to seasonal changes in reproduction are well-documented. Further elucidation of the physiological mechanisms driving these seasonal changes is needed. Two experiments were conducted in an attempt to further our understanding of seasonality in mares. In other seasonal species, such as sheep and goats, simply exposing anestrous females to sexually active males increases gonadotropin secretion within minutes, followed by ovulation 2 to 8 d later. This “male effect” was investigated in anestrous mares. In late February, mares were stratified by parity and age and assigned randomly to 1 of 3 treatments (n=7 per treatment): (1) DXP (direct exposure; mares housed adjacent to stallion and allowed direct contact for 2 h on 3 d/wk by placing the stallion into a cage in the center of a tease pen); (2) IXP (indirect exposure; mares housed adjacent to stallion but not allowed direct contact); and (3) CON (control; mares housed away from stallion and not allowed direct or indirect exposure). Ovarian activity was monitored thrice weekly until ovulation. During the first, third, and fifth days of treatment, blood was collected hourly for 8 h beginning just before treatment initiation for later analysis of LH and PRL. Interval from treatment initiation to ovulation did not differ (P > 0.05) among treatments. No effect (P > 0.05) of treatment was detected for LH or PRL concentrations, but a significant effect of day (P < 0.05) was observed with LH concentrations being greater on the fifth exposure day compared with the first and third. Endogenous opioid peptides have been shown to be involved in seasonal regulation in mares, both at the hypophysis and ovarian levels. The objective of this second study was to investigate the effects of an opioid antagonist, both alone and in combination with a GnRH agonist, on gonadotrophic hormone concentrations in transitional mares exposed to various progesterone environments. Seventeen stock-type, transitional mares were treated orally with altrenogest for 15 days. Mares were stratified by age and parity and assigned randomly to 3 treatments: (1) NAL (0.5 mg/kg BW naloxone hydrochloride IV, n = 5); (2) DES (1.8 mg deslorelin acetate IM, n = 6); or (3) N&D (naloxone hydrochloride followed by deslorelin acetate after 45 min, n = 6). Assigned treatment was administered 3 times during the study: (1) phase 1 (P1) occurred on the last day of altrenogest; (2) phase 2 (P2) occurred upon detection of a follicle ≥ 35 mm; and (3) phase 3 (P3) occurred 7 d post-ovulation. Interval from P1 to P2 was shorter (P < 0.05) for N&D compared with NAL, but not for any other treatment combinations. Interva from P2 to ovulation was not different (P > 0.05). Significant effects of phase and time were identified, with treatment initiating a greater (P < 0.05) LH response during P3 compared with P1 and P2. The FSH response to treatment was greater (P < 0.05) during P1 and P3 compared with P2. Regardless of phase, deslorelin increased both gonadotropins whereas naloxone alone only resulted in a biologically significant increase in gonadotropins during P3.
Keywords: transitional; seasonality; gonadotropin; physiologymare